2010
DOI: 10.1111/j.1365-3040.2009.02079.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cooling triggers forisome dispersion just before phloem transport stops

Abstract: Phloem transport stops transiently within dicot stems that are cooled rapidly, but the cause remains unknown. Now it is known that (1) rapid cooling depolarizes cell membranes giving a transient increase in cytoplasmic Ca 2+, and (2) a rise of free calcium triggers dispersion of forisomes, which then occlude sieve elements (SEs) of fabacean plants. Therefore, we compared the effects of rapid chilling on SE electrophysiology, phloem transport and forisomes in Vicia faba. Forisomes dispersed after rapid cooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…Initially, we observed intact sieve tubes for several hours by epifluorescence and confocal microscopy without any indication of dynamic behavior of SEOR1 bundles and agglomerations. Then, we tested different injury stimuli that are known to trigger the forisome reaction, such as local mechanical injury, distant burning of leaf tips, and local cold shocks (Furch et al, 2007;Thorpe et al, 2010). None of the treatments triggered any immediate reaction.…”
Section: Seor1 Functionmentioning
confidence: 99%
“…Initially, we observed intact sieve tubes for several hours by epifluorescence and confocal microscopy without any indication of dynamic behavior of SEOR1 bundles and agglomerations. Then, we tested different injury stimuli that are known to trigger the forisome reaction, such as local mechanical injury, distant burning of leaf tips, and local cold shocks (Furch et al, 2007;Thorpe et al, 2010). None of the treatments triggered any immediate reaction.…”
Section: Seor1 Functionmentioning
confidence: 99%
“…To determine whether roots effectively compete with defense-induced primary and secondary metabolites for carbon resources, root chilling treatments were used to disrupt carbon flow between above-and belowground tissues. The inhibition of phloem transport by chilling roots has been particularly well investigated (Geiger, 1969;Minchin et al, , 1994Poiré et al, 2010;Thorpe et al, 2010) and can be accomplished with minor drops in temperature . In our experiments, individual plants were seated inside an epoxy-sealed pot affixed in an ice water bath (0°C; Supplemental Fig.…”
Section: Root Chilling Treatmentmentioning
confidence: 99%
“…Considerable evidence indicates that low temperatures slow phloem transport and increase foliar sugar concentrations (e.g., Keskitalo et al 2005;Thorpe et al 2010). Other studies have repeatedly linked sugar enhancement to anthocyanin production (Hiratsuka et al 2001;Hara et al 2003), including among woody species under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, drought conditions (Gebre and Tschaplinski 2002), as well as pathogen infection (Bolouri Moghaddam and Van den Ende 2012), can also result in an accumulation of foliar soluble sugars and anthocyanins. In particular, it is well established that low-temperature exposure slows and can even halt phloem transport, thereby leading to foliar sugar buildups (e.g., Keskitalo et al 2005;Thorpe et al 2010). Mechanical disruption of the phloem can increase anthocyanin expression in a range of plant forms (e.g., Hughes et al 2005), and previous research showed that girdling sugar maple (Acer saccharum Marsh.)…”
Section: Introductionmentioning
confidence: 99%